Reinforcement of nanoglasses by interface strengthening. (December 2017) - Kalcher, Constanze; Adjaoud, Omar; Rohrer, Jochen; Stukowski, Alexander; Albe, Karsten
Abstract: Nanoglasses consist of glassy grains connected by an amorphous interface. While internal interfaces in nanoglasses help to prevent brittle failure, they are usually not beneficial to the glasses overall strength. In this molecular dynamics study, we manipulate the glass–glass interfaces of a Cu–Zr nanoglass, such that they are replaced by stronger crystalline interphases. Analogous to grain boundary strengthening in crystalline materials, we show that it is possible to reinforce the nanoglass without compromising its ductility. Graphical Abstract: